2002
DOI: 10.1021/jp021641e
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Hydrogenation over Platinum Nanoparticle Array Model Catalysts Fabricated by Electron Beam Lithography:  Determination of Active Metal Surface Area

Abstract: Pt nanoparticle array model catalysts with 28 ( 2 nm diameters and 100 ( 2 nm interparticle spacing have been fabricated with electron beam lithography on alumina supports. A novel method for cleaning the Pt nanoparticle arrays, involving low dosages of NO 2 and CO and mild temperature flashing, was established. This cleaning procedure was crucial for measuring reaction rates over the nanoparticle arrays. The reactivity of the Pt/Al 2 O 3 arrays was compared to a Pt(111) single crystal for the ethylene hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 21 publications
5
126
1
4
Order By: Relevance
“…Ordered two-dimensional arrays of monometallic or metal/oxide bifunctional nanocrystals have been prepared as model catalysts via electron lithography 13 and drop-casting 14 respectively, but afford extremely low surface areas with co-located active sites. Hence, there are no synthetic routes able to control either the nanoscale spatial distribution, or the communication between, individual functions within three-dimensional porous solids.…”
mentioning
confidence: 99%
“…Ordered two-dimensional arrays of monometallic or metal/oxide bifunctional nanocrystals have been prepared as model catalysts via electron lithography 13 and drop-casting 14 respectively, but afford extremely low surface areas with co-located active sites. Hence, there are no synthetic routes able to control either the nanoscale spatial distribution, or the communication between, individual functions within three-dimensional porous solids.…”
mentioning
confidence: 99%
“…This field developed rapidly by use of model catalysts, first single-crystal surfaces (7)(8)(9)(10)(11)(12), then monodispersed nanoclusters deposited on oxide surfaces by lithography techniques (13)(14)(15)(16)(17) (Fig. 1).…”
mentioning
confidence: 99%
“…Small Pt particles as well as large Pt particles showed catalytic activity in deuteration of ethene with turnover rates comparable to literature values. 53 The small particles exhibited a deactivation period in the first 10 min of reaction that was not related to particle sintering or particle shape changes, but most likely to changes in the morphology of the particles. 47 The decrease in the white line intensity with increasing temperature during the reaction on small particles reflects an increase in the electron density of the particles.…”
Section: Resultsmentioning
confidence: 93%
“…A stable ethene conversion of 0.12% and 0.08% was determined for small and large Pt particles, respectively, in good accord with the results obtained on B15 nm sized Pt particles tested under similar conditions. 53 The Pt-metal loading-based ethane turnover rates were 22 The GISAXS study during the deuterium-ethene reaction showed that small Pt particles on n-GaN changed their shape reversibly, while large particles were not affected. The decreased lateral diameter of small particles in reactant gas atmosphere is attributed to rearrangements of particle facets.…”
Section: Hydrogenation Of Ethene With Deuteriummentioning
confidence: 99%